Dynamic analysis of chevron structures in liquid crystal cells. (13th April 2017) - Mrad, Lidia; Phillips, Daniel
ABSTRACT: If a surface stabilized ferroelectric liquid crystal cell is cooled from the smectic-A to the smectic-C phase its layers thin causing V-shaped (chevron like) defects to form. These create an energy barrier that can prevent switching between equilibrium patterns. We examine a gradient flow for a mesoscopic Chen-Lubensky energy that allows the order parameter to vanish, so that the energy barrier does not diverge if the layer thickness becomes small. The liquid crystal can evolve during switching in such a way that the layers are allowed to melt and heal near the chevron tip in the process.